Effectiveness of the Collaborative Learning Model in Writing Biographical Texts for Students - Muhtasar Ayudi; Burhanudin Burhanudin; Ahmad Sirulhaq; Saharudin Saharudin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to determine the effectiveness of the collaborative learning model in improving the ability to write biographical texts among tenth-grade students at MA NW Dasan Lian. The background of this research stems from the students’ low interest and poor quality in writing biographical texts, which are often unstructured and lack creativity. The collaborative learning model was chosen because it is believed to enhance active student engagement through teamwork, discussion, and mutual feedback during the learning process. This research employs a quantitative approach with a quasi-experimental design. The instruments used were pre-test and post-test writing assignments. The results show a significant improvement in students’ biographical writing after the implementation of the collaborative learning model, as evidenced by the difference between pre-test and post-test scores analyzed using a t-test. Therefore, the collaborative learning model is proven effective in enhancing students’ biographical writing skills. The study recommends the use of collaborative learning as an alternative strategy in teaching writing at the secondary education level